Pericytes promote skin regeneration by inducing epidermal cell polarity and planar cell divisions. - Zhuang, L.; Lawlor, K.; Schlueter, H.; Pieterse, Z.; Yu, Y.; Kaur, Pritinder (2018)
The cellular and molecular microenvironment of epithelial stem/progenitor cells is critical for their long-term self-renewal. We demonstrate that mesenchymal stem cell-like dermal microvascular pericytes are a critical element of the skin's microenvironment influencing human skin regeneration using organotypic models. Specifically, pericytes were capable of promoting homeostatic skin tissue renewal by conferring more planar cell divisions generating two basal cells within the proliferative compartment of the human epidermis, while ensuring complete maturation of the tissue both spatially and temporally. Moreover, we provide evidence supporting the notion that BMP-2, a secreted protein preferentially expressed by pericytes in human skin, confers cell polarity and planar divisions on epidermal cells in organotypic cultures. Our data suggest that human skin regeneration is regulated by highly conserved mechanisms at play in other rapidly renewing tissues such as the bone marrow and in lower organisms such as Drosophila. Our work also provides the means to significantly improve ex vivo skin tissue regeneration for autologous transplantation.